Factors Affecting the Decision of Patients to Utilize Health Services for Recycling - Dherma Wati Bangun; Dherma Wati Bangun; Vivi Eulis Diana (Newinera Publisher, 2021)
Patients in health services have different behaviors in deciding to take advantage of health services. Patients used various considerations to make decisions based on the health products or services for re-treatment. The study aimed to analyze the factors that influence the patient's decision in using health services for re-treatment. This research was quantitative with cross-sectional design and conducted at Tanjung Pura Regional Hospital. The population was 3.946 people, and the sample were 247 respondents taken by using purposive sampling. Data analysis was univariate and bivariate using chi-square and multivariate using multiple logistic regression at the 95% confidence level (a= .05). The results showed that the factors that influenced the patient's decision to use health services for re-treatment at the Tanjung Pura Regional Hospital were the service quality of doctors / nurses (p= .000), distance (p=.049), facilities (p=0.000), and service speed (p = .000). The factors that did not influence we age (p=.461). gender (p=.895), education (p=.371), occupation (p=.593). The most dominant factor influencing is facilities with Exp (B)/OR =14.477, meaning that respondents who stated that the hospital facilities were good, had the opportunity to use health services for re-treatment by 14.4 times higher the respondents who stated that the hospital facilities were not good. It is suggested to Tanjung Pura Regional Hospital to propose and allocate a budget for improving hospital facilities that are still lacking and adding new service facilities so that it can increase public confidence for repeat treatment